MARKET BASKET ANALYSIS PADA MOBILE CUSTOMER RELATIONSHIP MANAGEMENT - Susanto Putro, Adi Nugroho S; ., Ernawati; Wisnubhadra, Irya (Proceeding SENDI_U, 2015)
CV. Anugerah is a retail company in Solo which has four branches. CV. Anugerah sells products of stationery,clothes, and various accessoris. CV. Anugerah has 5.784 items things that every day are evenly 926 items sold.Some problems that CV. Anugerah often faces are there are many kinds of things sold there, the brand of the thingsfrequently changes into other brands; it makes the customers and the shokeepers frequently confused. To find thethings they need, it takes long time. A supermarket manager can learn more about the customersâ âshoppingpattern.â Market Basket Analysis can be done on the data of retail customersâtransaction in the shop. The results ofthe analysis can be used to plan the markerting strategy or the advertisement and also the shop layout catalog design.Customer relationship management (CRM) has been broadly assumed as one methodology and organization processto interest and defend the customers through improving customersâ satisfaction and loyality. CRM technologies arecategorized into: Collaborative, Operational and Analytical. This research will develop a Market Basket Analysis onMobile Customer Relationship Management which can be used by management party of CV. Anugerah as theOperational and Analytical CRM in real time by mobile device. By creating this system, it is hoped that it canincrease the service and the turnover of CV. Anugerah Group.Keywords : Analisis Keranjang Pasar, FP-Growth, Mobile CRM